Anatomy of cerebral veins and sinuses - (:unkn) unknown (My University, 2008)
The veins of the brain have no muscular tissue in their thin walls and possess no valves. They emerge from the brain and lie in the subarachnoid space. They pierce the arachnoid mater and the meningeal layer of the dura and drain into the cranial venous sinuses. The cerebral venous system can be divided into a superficial and a deep system. The superficial system comprises sagittal sinuses and cortical veins, which drain superficial surfaces of both cerebral hemispheres. The deep system consists of the lateral sinus, straight sinus and sigmoid sinus along with draining deeper cortical veins. Both of these systems mostly drain into internal jugular veins. Generally, venous blood drains into the nearest venous sinus or, in the case of blood draining from the deepest structures, into deep veins. The superficial cerebral veins are interlinked with anastomotic veins of Trolard and Labbé. Thus, the superolateral surface of the hemisphere drains into the superior sagittal sinus while the posteroinferior aspect drains into the transverse sinus. The veins of the posterior fossa are variable in course, and angiographic diagnosis of their occlusion is difficult. The entire deep venous system is drained by internal cerebral and basal veins, which join to form the great vein of Galen that drains into the straight sinus. Though variation in the superficial cerebral venous system is a rule, anatomic configuration of the deep venous system can be used as anatomic landmarks. Since thrombosis or surgical sacrifice of the cerebral veins may lead to venous infarction with serious complications, angiographic and surgical anatomy of the venous system should be seriously investigated for each individual patient.
Keywords: Humans; Cranial Sinuses; Cerebral Veins